DEVELOPMENT OF COMMUNICATIVE COMPETENCE IN 1ST GRADE STUDENTS BY MEANS OF EDUCATIONAL GAME - Ivasyuk, Maria (Mountain School of Ukrainian Carpaty, 2020)
In the article the problem of peculiarities of formation of communicative competence of first grade students with the help of educational games is analyzed. The initial level of formation of communication skills and abilities of schoolchildren is experimentally researched. The difference between the concepts of «communicative competence» and «language competence» is determined. The peculiarities are analyzed and the main ways of using games in the educational process for developing primary school students’ communicative competence are determined. The influence of educational games on the level of formation of communicative competence is characterized. It is noted that communicative competence affects not only mastering the required amount of language and speech knowledge, but also the process of forming primary school students’ skills of practical use of language in speech and reflects their skills of communicating with others and ability to choose communication strategies and apply a set of relevant skills. The process of formation of communicative competence of 1st grade students involves mastering the skills and abilities of using means of verbal and nonverbal speech; development of dialogic and monologue speech; mastering the culture of oral and written speech and development of skills to navigate in a variety of communicative situations. It has been proved that educational games, because of repeated perception and reproduction of the material, provide strong memorization of lexical units and grammatical structures and influence motivated transfer and use in new gamequalities necessary for establishing contacts with peers. The pedagogical requirements for the use of didactic games during morning meetings and lessons in primary school are determined. In particular, it has been researched that games must correspond to age, individual characteristics and special educational and, in particular, language abilities; the form and content of the game must be substantiated pedagogically and didactically; it is obligatory to involve as many children as possible in the game and to use games in order to develop all kinds of speech activities. The article describes the author’s own pedagogical experience and provides guidelines for the use of educational games in the primary school educational process.